Avaliação objetiva e subjetiva de idosos usuários de próteses auditivas segundo o desempenho cognitivo e os sintomas depressivos - Carvalho, Laura Maria Araújo de [UNIFESP] (2009)
Purpose: To evaluate the performance of experienced hearing aid users using sentence recognition in noise tests and self-assessment questionnaires considering cognitive performance, period of hearing aid user, educational level and age. Method: Twenty-five hearing impaired elderly, male and female, experienced binaural hearing aid users were selected. All subjects were evaluated in one session of 90 minutes. A subjective evaluation of cognitive abilities was performed using Mini Exam of Mental State (MEMS) and Alzheimer’s Disease Global Assessment Scale – Cognitive (ADAS-Cog), one to detect depressive state (Geriatric Depression Scale - GDS) and a last one to evaluate the benefits of hearing aid adaptation (IOI-HA). Finally, the Sentence Recognition in Noise Test was administered binaurally in free field order to evaluate speech recognition by varying signal-to-noise ratio (S/N). All subjects have undergone the test wearing their own hearing aids which were dispensed at least three months early. Statistical analysis included dispersion diagrams with their respective lowess curves and Spearmann correlation. Results: Results analysis revealed no correlation among tests scores – MEEM, Adas-Cog, IOI-HA, GDS and signal-to-noise ratio and age and period of hearing aid use. Considering educational level, significant correlations were observed in the scores of MEEM, Adas-Cog, IOI-HA, GDS and Signal-to-noise ratio. In the correlation among the tests, a significant correlation was observed between signal-to-noise ratio and scores of MEEM, Adas-Cog and GDS, and also correlation between Adas-Cog and MEEM and GDS scores. Conclusion: There is no contribution of depressive symptoms, age and period of hearing aid use to explain signal-to-noise ratio. The better the cognitive and educational levels the better the performance in noise.